PENGARUH USAHA MIKRO KECIL MENENGAH TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN BERAU: PENGARUH USAHA MIKRO KECIL MENENGAH TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN BERAU - IRA INDRIANI (ECO-BUILD, 2022)
The purpose of writing this thesis is to know the influence of Micro, Small and Medium Enterprises on Economic Growth in Berau Regency. This research is a research that uses quantitative data, namely primary data. By means of simple linear regression analysis, correlation analysis (r), t test (partial), correlation coefficient, coefficient of determination and t test which will be processed using SPSS version 25.0 program. The results showed that the variable Micro, Small and Medium Enterprises (MSMEs) (X) had an effect on the variable Economic Growth (Y) but it was not significant because the value was greater than 0.5% and it was known that the t arithmetic value was 1.805 > t table 2.132 so it can be concluded that The variable of Micro, Small and Medium Enterprises (MSMEs) has an effect but is not significant on the variable of Economic Growth (Y). Then the value of the coefficient of determination (R2) of 0.449 (MSMEs) in Berau Regency is 44.9% and the rest is influenced by other variables or factors that are not examined in this model. It is hoped that the Government as a policy maker will pay more attention to existing MSMEs, namely by empowering MSMEs such as granting permits, capital assistance, and so on. Because MSMEs in Berau Regency have good potential for regional progress so that in the long term they can help increase regional economic growth